Preparation Of Financial Reports And Fulfillment Of Obligations And Taxes Of Village Owned Enterprises (BUMDES) - Ludigdo, Unti; Puspita, Ayu Fury; Damayanti, Made Tara; Lase, Maria Inggried Soinia; Mufid, Muhammad Farras (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2024)
BUMDes or Village-Owned Enterprises are business entities originating from Village assets which are separated to manage assets, services, and other businesses for the greatest welfare of the Village community. BUMDes was formed in order to help villages increase village original income, through the Regulation of the Minister of Villages, Disadvantaged Regions and Transmigration Number 4 of 2015 concerning the Establishment, Management and Management, and Dissolution of Village-Owned Enterprises in which there is an explanation that the village government can establish BUMDes. According to Article 12 paragraph (3) of the Regulation of the Minister of Villages, Development of Disadvantaged Regions and Transmigration Number 4 of 2014 that the BUMDes Operational Implementer is required to make Financial Reports of all business units every month as an accountability to the Village Government. So far, BUMDes managers have routinely reported as a form of their accountability. However, these financial reports are often not in accordance with what has been used as the proper standard for the Financial Reporting Guidelines/Accounting Standards. Therefore, it is necessary to hold socialization regarding the preparation of BUMDes financial and tax reports. This community service was carried out to 30 BUMDes in Junrejo District. The results showed that more than 40% of the participants felt helped by the event with this theme.